Main stages in the development of the concept of the head of state as a guarantor of statehood in the history of European political and legal thought - Shcherbik, Dmitrii V. (Journal of the Belarusian State University. Law, 2022)
The author examines the development of views on the essence and appointment of the head of state as a guarantor of statehood in the history of political and legal thought of European states. The evolution of ideas about the connection between the power of the head of state and the need to ensure peace, security and justice in society, his role in resolving emergency situations for the existence of the state is traced. The author identifies the main stages in the development of the concept of the head of state is the guarantor of the constitution, lists the distinctive features of these stages. For each of them, the features of ideas about the powers of the head of state in this area are noted.